1998
DOI: 10.1051/limn/1998029
|View full text |Cite
|
Sign up to set email alerts
|

Variations nycthémérales de l'activité phosphatase alcaline d'une Diatomée :Synedra capitataet de deux Cyanobactéries :Microcystis aeruginosaetAphanizomenon flos aquae

Abstract: The results we present here were on three quasi monospecific settlements : Synedra capitata (Diatom), Microcystis aeruginosa and Aphanizomenon flos aquae (Cyanobacteria). The alkaline phosphatase activity (APA) (EC : 3.1.3.1) exhibited a nycthemeral variation for Diatoms as well as Cyanobacteria, though every species had its own characteristic. Under similar experimental conditions, the enzymatic activity was, in the average, 32 times higher (per unit of biomass) for Microcystis aeruginosa than for Synedra cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…APA studies have mainly focused on algae (Healey, 1973;Giraudet et al, 1998;Spijkerman & Coesel, 1998;Nedoma et al, 2003), and have scarcely dealt with zooplankton activity, even though zooplankton is also known to release AP (Rigler, 1961;Jansson, 1976;Wynne & Gophen, 1981;Boavida & Heath, 1984;Jansson et al, 1988;Jamet & Boge, 1998;Hoppe, 2003;Jean et al, 2003). The predominant phosphatase released by zooplankton was found to be alkaline phosphatase, but it also released some acid phosphatase.…”
Section: Introductionmentioning
confidence: 99%
“…APA studies have mainly focused on algae (Healey, 1973;Giraudet et al, 1998;Spijkerman & Coesel, 1998;Nedoma et al, 2003), and have scarcely dealt with zooplankton activity, even though zooplankton is also known to release AP (Rigler, 1961;Jansson, 1976;Wynne & Gophen, 1981;Boavida & Heath, 1984;Jansson et al, 1988;Jamet & Boge, 1998;Hoppe, 2003;Jean et al, 2003). The predominant phosphatase released by zooplankton was found to be alkaline phosphatase, but it also released some acid phosphatase.…”
Section: Introductionmentioning
confidence: 99%
“…According to Petterson (1980), the primary portion of APA is particulate, but Stewart and Wetzel (1982) demonstrated that at least 50% of the total APA is the result of enzymes in the dissolved fraction. Phosphatase activity has also been shown to vary with the trophic status of the lake (Olsson, 1990) and the taxonomic composition of the phytoplankton (Giraudet et al, 1998, andRivkin andSwift, 1979) or bacteria (Chrost et al, 1986) communuities. Berman (1970) found that phytoplankton were significant contributors to the total APA, whereas Stewart and Wetzel (1982) attributed all of the activity to bacteria.…”
Section: Introductionmentioning
confidence: 99%